Building a Scout Public Service Scale for first-year students in the faculties of physical education and sports sciences - Ilad Mohammed; Dr. Iqbal Abdul-hussein (physical education and sport sciences college for women/ Baghdad University, 2021)
The importance of the study lies in building the Scout Public Service Scale for first-year students in the faculties of physical education and sports sciences.The research aimed to: Building the Scout public service standards for the first-year students of the faculties of physical education and sports sciences in the universities of the Middle Euphrates. The two researchers used the descriptive approach in the style of the survey study to identify the scouting public service for the students of the first stage of the faculties of physical education and sports sciences in the universities of the Middle Euphrates (Kufa, Al-Qadisiyah, Babylon, Al-Qasim Al-Khadra, and Kerbala) for the academic year 2020-2021, which numbered (624) male and female students.The sample of the exploratory experiment for the Scout Public Service Standards consisted of (15) students, at a rate of (5.68%) from the research community.They were chosen by random method, and a sample was chosen to build the two Scout public service scales, consisting of (250) male and female students (40.06%) from the research community, with (50) male and female students from each college.As for the application sample of the Scout Public Service Standards, it included (100) students, (20) male and female students from each college representing (16.02%) of the research community. Under the results of the current research, and the subsequent explanations, we can come up with several conclusions, the most